Effects of salinity and high temperature stress on winter wheat genotypes - Ehtaiwesh, Amal Faraj Ahmed (Kansas State University, 2016)
Increased ambient temperature and soil salinity seriously affect the productivity of wheat (Triticum aestivum L.) which is an important cereal second to rice as the main human food crop. However, wheat plant is most susceptible to high temperatures and salinity at booting and flowering stages. Several studies have documented the effects of individual stress like salinity and high temperature stress on wheat, nonetheless little is known about effects of combined salinity and high temperature at critical growth stages. Therefore, the objectives of this research were (i) to screen winter wheat germplasm for salinity tolerance at the germination stages and to determine seedling growth traits associated with salinity tolerance, (ii) to evaluate the independent and combined effects of high temperature and salinity on winter wheat genotypes at the booting stages through growth, physiological, biochemical, and yield traits, and (iii) to evaluate the independent and combined effects of high temperature and salinity on winter wheat genotypes at the flowering stages through growth, physiological, biochemical, and yield traits. In the first experiment, 292 winter wheat genotypes (winter wheat germplasm) was screened for salinity stress at germination stage under controlled environments. The seeds were subjected to three levels of salinity, 0, 60, and 120 mM NaCl to quantify the effects of salinity on seed germination and seedling growth. In the second experiment, controlled environment study was conducted to quantity the independent and combined high temperature and salinity stress effects on growth, physiological, biochemical, and yield traits of twelve winter wheat genotypes during booting stage. Plants were grown at 20/15 °C (daytime maximum/nighttime minimum) temperature with 16 h photoperiod. At booting stages, the plants were exposed to optimum (20/15 °C) or high temperature (35/20 °C) and without (0 mM NaCl) and with (60, and 120 mM) NaCl. In the third experiment, plants were exposed to optimum or high temperature and with and without NaCl levels at flowering stages. The temperature regime and salinity levels were same as experiment II. The duration of stress was 10 d and after the stress period the plants were brought to optimum temperature and irrigated with normal water (0 mM NaCl). The results indicated that, at 120 mM NaCl, the final germination percentage was decreased and the mean daily germination was delayed. Irrespective of the genotype, salinity stress significantly decreased the shoot and root length; seedling dry matter production, and seedling vigor. Based on the seedling vigor index, the genotype GAGE, OK04507, MTS0531, TASCOSA, ENDURANCE and GUYMON, were found to be most tolerant and CO04W320, 2174-05, CARSON, OK1070275, TX02A0252 and TX04M410211 were the most susceptible to salinity at germination stage. Combined stresses of high temperature and salinity decreased photosynthetic rate and grain yields. Based on grain yield, the genotype TASCOSA was found to be most tolerant (64 % decrease) to combined stresses, and AVALANCHE was the most susceptible to combined stresses (75 % decrease) at booting stages. Similarly, at flowering stage, TX04M410211 had greater tolerance to combined stresses (65 % decline) as compared to GAGE (83 % decline). In both experiments, tolerance was associated with higher spikelet number and seed set. In conclusion, there is genetic variability among winter wheat genotypes that can be used in breeding programs to improve winter wheat yield under combined high temperature and salinity stress conditions.
Keywords: Wheat; Salinity; High temperature